Engineering energy storage - Burheim, Odne Stokke (Academic Press, 2017)
Engineering Energy Storage explains the engineering concepts of different relevant energy technologies in a coherent manner, assessing underlying numerical material to evaluate energy, power, volume, weight and cost of new and existing energy storage systems. With numerical examples and problems with solutions, this fundamental reference on engineering principles gives guidance on energy storage devices, setting up energy system plans for smart grids. Designed for those in traditional fields of science and professional engineers in applied industries with projects related to energy and engineering, this book is an ideal resource on the topic.